2000
DOI: 10.1002/1096-9888(200009)35:9<1128::aid-jms41>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of an automated chromium reduction system for hydrogen isotope ratio analysis of physiological fluids applied to doubly labeled water analysis

Abstract: The doubly labeled water method is commonly used to measure total energy expenditure in free-living subjects. The method, however, requires accurate and precise deuterium abundance determinations, which can be laborious. The aim of this study was to evaluate a fully automated, high-throughput, chromium reduction technique for the measurement of deuterium abundances in physiological fluids. The chromium technique was compared with an off-line zinc bomb reduction technique and also subjected to test-retest analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 19 publications
(29 reference statements)
2
36
0
Order By: Relevance
“…Saliva samples were collected before dosing, as well as at 3 and 4 hours after dosing. 2 H level in the saliva samples was measured by gas-isotope-ratio mass spectrometry 7,8 . Deuterium dilution space was calculated from the average of two post-dose saliva samples by the plateau method.…”
Section: Methodsmentioning
confidence: 62%
“…Saliva samples were collected before dosing, as well as at 3 and 4 hours after dosing. 2 H level in the saliva samples was measured by gas-isotope-ratio mass spectrometry 7,8 . Deuterium dilution space was calculated from the average of two post-dose saliva samples by the plateau method.…”
Section: Methodsmentioning
confidence: 62%
“…Abundances of H 2 18 O and 2 H 2 O in dilutions of the isotope doses and in urine specimens were measured in duplicate using isotope ratio mass spectrometry [36] and deuterium was prepared for analysis using an automated chromium reduction system [37]. The urine samples were analyzed at the Pennington Biomedical Research Center (Baton Rouge, LA).…”
Section: Total Energy Expenditure (Tee)mentioning
confidence: 99%
“…Isotope ratio mass spectrometers are generally priced in excess of several hundred thousand dollars (US), but price reductions may be possible in the future if manufactures can redesign the instrumentation with the goal of developing specific task instruments. Recent improvements in design, particularly of on-line water analysis systems, have dramatically improved sample throughput from several samples per hour to a sample every 10 minutes 26 . It has generally been observed that one to three years of experience is required to obtain optimal laboratory performance, although new technicians working in an existing laboratory can learn to use the modern instruments for routine analyses within weeks.…”
Section: Isotopic Analysismentioning
confidence: 99%